Rewiring a secondary metabolite pathway towards itaconic acid production in Aspergillus niger. Issue 1 (December 2016) - Hossain, Abeer; Li, An; Brickwedde, Anja; Wilms, Lars; Caspers, Martien; Overkamp, Karin; Punt, Peter
Abstract Background The industrially relevant filamentous fungusAspergillus niger is widely used in industry for its secretion capabilities of enzymes and organic acids. Biotechnologically produced organic acids promise to be an attractive alternative for the chemical industry to replace petrochemicals. Itaconic acid (IA) has been identified as one of the top twelve building block chemicals which have high potential to be produced by biotechnological means. The IA biosynthesis cluster (cadA, mttA andmfsA ) has been elucidated in its natural producerAspergillus terreus and transferred toA. niger to enable IA production. Here we report the rewiring of a secondary metabolite pathway towards further improved IA production through the overexpression of a putative cytosolic citrate synthasecitB in aA. niger strain carrying the IA biosynthesis cluster. Results We have previously shown that expression ofcadA fromA. terreus results in itaconic acid production inA. niger AB1.13, albeit at low levels. This low-level production is boosted fivefold by the overexpression ofmttA andmfsA in itaconic acid producing AB1.13 CAD background strains. Controlled batch cultivations with AB1.13 CAD + MFS + MTT strains showed increased production of itaconic acid compared with AB1.13 CAD strain. Moreover, preliminary RNA-Seq analysis of an itaconic acid producing AB1.13 CAD strain has led to the identification of the putative cytosolic citrate synthasecitB which was induced in an IA producing strain. We have overexpressedcitB in a AB1.13 CAD + MFS + MTT strain and by doing so hypothesize to have targeted itaconic acid production to the cytosolic compartment. By overexpressingcitB in AB1.13 CAD + MFS + MTT strains in controlled batch cultivations we have achieved highly increased titers of up to 26.2 g/L IA with a productivity of 0.35 g/L/h while no CA was produced. Conclusions Expression of the IA biosynthesis cluster inAspergillus niger AB1.13 strain enables IA production. Moreover, in the AB1.13 CAD strain IA production resulted in overexpression of a putative cytosolic citrate synthasecitB . Upon overexpression ofcitB we have achieved titers of up to 26.2 g/L IA with a productivity of 0.35 g/L/h in controlled batch cultivations. By overexpressingcitB we have also diminished side product formation and optimized the production pathway towards IA.